Estudo ab-initio da a-alanina em meio aquoso - Sambrano, Julio Ricardo [UNESP]; Souza, Aguinaldo Robinson de [UNESP]; Queralt, Joaquim Josep; Andrés, Juan; Longo, Elson [UNESP] (Sociedade Brasileira de Química, 1999)
Ab initio Hartree-Fock (HF), Density Functional (B3LYP) and electron correlation (MP2) methods have been used to caracterize the aqueous medium intramolecular hydrogen bond in a-alanine. The 6-31G* and 6-31++G** were taken from Gaussian94 library. We were concerned on the structure of three conformers of a-alanine, in their neutral form plus on the structure of the zwitterionic form (Z). The Z structure is a stationary point at the HF/6-31G* level but it is not when diffuse functions and electron correlation are included. This results shows that the Z form does not exist in the gas phase. The inclusion of solvent effects changed significantly the results obtained in gas phase, therefore this inclusion make the Z form a stationary point within all level of theory, and the relative energy depends dramatically on the level of calculation.
Ab-initio study of a-alanine in aqueous medium
Keywords: ab initio; a-alanine; solvent